Ultrafast Tm-doped fiber laser system delivering 1.65-mJ, sub-100-fs pulses at a 100-kHz repetition rate - Heuermann, Tobias; Wang, Ziyao; Lenski, Mathias; Gebhardt, Martin; Gaida, Christian; Abdelaal, Mahmoud; Buldt, Joachim; Mueller, Michael; Klenke, Arno; Limpert, Jens (Optics Letters, 2022)
High-energy, ultrafast, short-wavelength infrared laser sources with high average power are important tools for industrial and scientific applications. Through the coherent combination of four ultrafast thulium-doped rod-type fiber amplifiers,we demonstrate a Tm-doped chirped pulseamplification system with a compressed pulse energy of 1.65 mJ and 167W of average output power at a repetition rate of 101 kHz. The system delivers 85 fs pulses with a peak power of 15GW. Additionally, the system presents a high long- and short-term stability. To the best of our knowledge, this is the highest average output power short wavelength IR, mJ-class source to date. This result shows the potential of coherent beam combining techniques in the shortwavelength infrared spectral region for the power scalability of these systems.
CRIS-Team Scopus Importer:2023-04-20